Plant disease detection using convolutional neural network - Hossain, Mohammad Shifat; Noor, Fatin Ishraq; Ali, Mir Ayman; Alam, Ra ul (Brac University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2020.